Pekerja Anak di Kawasan Timur Indonesia Tahun 2022: Kondisi dan Faktor yang Memengaruhi - Al Muflih, Muhammad Rafii; Wijaya, Yuliagnis Transver (UI Scholars Hub, 2024)
In 2019-2022, the percentage of child labor in eastern Indonesia has consistently been higher than in western Indonesia. However, research specifically focusing on child labor in eastern Indonesia is limited. This study aims to examine the conditions and factors influencing child labor in eastern Indonesia. Utilizing data from the August 2022 Indonesia National Labor Force Survey (Sakernas), the study employs descriptive analysis and binary logistic regression. Findings reveal that 5-6 out of 100 children in eastern Indonesia are engaged in child labor. Predominantly, they work in agriculture, forestry, and fisheries, though there are regions where most are employed in other sectors. Factors such as gender, age, school enrollment status, the educational level and occupation of the household head, marital status, position as the eldest child, household size, residential classification, the presence of other working children in the household, and the interaction between age and school enrollment status significantly influence child labor in eastern Indonesia. The government should establish specific programs or divisions within the Indonesian child protection commission at regional levels to collect data, mediate, and provide tailored solutions to effectively address child labor issues across different regions.